Síntese de 3 e 4-(organosselenil)-quinolinas via reações de ciclização intramolecular - Silva, Guilherme Lutz da (2024)
Quinolines are important heterocycles, where many molecules that have biological and pharmacological activities constitute this quinoline nucleus, driving more and more studies on the synthesis of these compounds. In the present work, a synthetic route was initially developed for preparing 4-organoselenyl-quinolines 2 derivatives. The methodology developed is based on an intramolecular cyclization reaction of β-(aminoaryl)-α,β -ynones 1 in the presence of nucleophilic organoselenium species generated by the mixture of sodium borohydride and diorganoyl diselenides. After a study in search of the best optimization condition, it was analyzed that the use of diaryl diselenide (1 equiv.) reacts with NaBH4 (1 equiv.) in DMF at 90º temperature, generating the nucleophilic species of organoselenium that react with β-(aminoaryl)-α,β-ynones 1 ensuring the best conversion of the starting materials into the desired products. The developed condition led to the formation of 21 4-organochalcogenyl-quinoline 2 compounds, whose yields ranged from 37% to 98%. Carrying out mechanistic studies indicated that the reaction begins with reducing the alkyne group of starting material 1 by arylselenol, leading to vinyl arylselenide, and, subsequently, cyclocondensation to form quinoline products. In the second step, a synthetic protocol was developed to prepare 4-iodo-3-organoselenyl-quinolines 3. This methodology involves a similar reaction to the previous one but uses an electrophilic selenium source to reduce β-(aminoaryl)-α,β-yones 1 and formation of products 3. The study of the best reaction condition demonstrated that diorganoyl diselenides (1 equiv.) react with (1 equiv.) I2 in DCM, to form organoselenenyl iodides, which react with the starting material 1, ensuring the best condition for forming products 3. The methodology developed was applied to different substrates, and, in the end, 17 new compounds of 4-iodo-3-organoselenyl-quinolines 3 were obtained in yields ranging from 51 to 95%. It is worth noting that, at the end of both protocols developed, some compounds obtained were selected to subject them to coupling reactions of the Suzuki, Ullmann, and Sonogashira type, as well as Lithium-Exchange reactions, generating a series of new compounds, emphasizing intramolecular electrophilic cyclization, promoted by molecular iodine, of the substrates 3-(butylselenyl)-6-methyl-2-phenyl-4-(phenylethynyl)quinolines 74, forming five new products of 1-iodo-8-methyl-4-phenylselenophen[ 2,3-c]quinolines 75, in yields 79% to 98%. Therefore, this work demonstrates a new efficient synthetic route for the synthesis of organoselenyl-quinolines, having excellent tolerability for different functional groups and providing the reactivity of these molecules in coupling reactions for the formation of new carbon-carbon bonds.